Evaluasi Kinerja Angkutan Penumpang Transportasi Penyeberangan Speedboat Reguler Rute Tarakan-Kabupaten Tana Tidung - Rohana Teguh Ning Tias; Muhammad Djaya Bakri (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2022)
Tarakan is home to the main seaport that serves all districts in North Kalimantan. Tana Tidung Regency is one of the regencies that serve the Tarakan feeder port route. This is supported by the presence of a Sesayap River network. To provide comfort to service users, the high demand for ferry transportation services must be balanced with adequate speedboat service facilities. Data was collected by distributing questionnaires and conducting interviews to determine the level of satisfaction of service users and the attributes that are a priority in improving the performance of speedboat services. The data collection results were analyzed using Importance Performance Analysis (IPA) dan Customer Satisfaction Index (CSI) methods. Then, to follow up on the results of the IPA dan CSI analysis, the Quality Function Deployment (QFD) method was used, a technique used to identify priorities for performance management based on the needs and desires of service users. Based on the results of the IPA analysis, three attributes were obtained as the top priority to require handling/improving their performance; the availability of fire extinguishers, the availability of information on speedboat travel disturbances, and the availability of boarding and alighting facilities for passengers with special needs, children, and pregnant women. The result of the CSI analysis obtained a service user satisfaction index of 63.379 which indicated that the service performance perceived by service users was decreased within the “Quite Satisfied” criteria. While the results of the QFD analysis obtained a priority sequence for improving/handling speedboat performance which was offloading the passengers by being carried out or stretchered, and access was categorized as the first priority, the second and third priorities were the availability of communication tools that were readily used by the captain and crew in the speedboat and notifications in the form of messanges to prospective passengers related to changes in departure schedules, and the last priority was the placement of APARs at 3 points, which was near from the diver or captain, passenger room, and the speedboat engine area.